Determination of the pre-consolidation effort from the liquidity index and the sensitivity of the clay soils of Pucallpa - Hernández Aguilar, Marco Antonio (2024)
Currently, the preconsolidation effort is generally determined from the one-dimensional consolidation test in the laboratory, whose procedure is too long and requires a lot of execution time, where one must wait between 10 to 15 days to obtain the results. However, the United States Department of the Navy has alternative theories and formulas to determine this parameter in a more practical way and in less time, based on the determination of the liquidity index and the sensitivity of the soil. Therefore, this research work will calculate the pre-consolidation effort based on the aforementioned methodology of fine soils (clay), a determining geotechnical parameter to calculate settlements due to consolidation when applying a load to a structure to be built. In this way, unaltered samples of clay soils well distributed in the city of Pucallpa have been tested, carrying out laboratory tests for identification and characterization of the evaluated samples, such as natural moisture content, liquid limit, plastic limit to determine their index of plasticity, in addition to simple or unconfined compression tests on unaltered and remoulded samples, necessary and sufficient data to obtain the Liquidity Index and sensitivity. The result of the research was to confirm a reliable alternative methodology, which requires less cost and time to determine the pre-consolidation effort, whose results obtained have been compared with various one-dimensional consolidation tests carried out in the laboratory with samples from different projects carried out in the study zone.